2023
DOI: 10.1136/bmjopen-2022-071344
|View full text |Cite
|
Sign up to set email alerts
|

How capacity building of district health managers has been designed, delivered and evaluated in sub-Saharan Africa: a scoping review and best fit framework analysis

Abstract: ObjectivesWe aimed to understand how capacity building programmes (CBPs) of district health managers (DHMs) have been designed, delivered and evaluated in sub-Saharan Africa. We focused on identifying the underlying assumptions behind leadership and management CBPs at the district level.DesignScoping review.Data sourcesWe searched five electronic databases (MEDLINE, Health Systems Evidence, Wiley Online Library, Cochrane Library and Google Scholar) on 6 April 2021 and 13 October 2022. We also searched for grey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…We collected data through a scoping review of the capacity building of district health managers in sub-Saharan Africa [ 31 ], a review of documents related to the PHA reform in the DRC and in-depth interviews with stakeholders of the PHA reform (Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We collected data through a scoping review of the capacity building of district health managers in sub-Saharan Africa [ 31 ], a review of documents related to the PHA reform in the DRC and in-depth interviews with stakeholders of the PHA reform (Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…We included all primary studies reporting leadership or management capacity building of district health managers in sub-Saharan Africa, written in English or French, and published between 1 January 1987 and 13 October 2022. Further details on the scoping review can be found elsewhere [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…We collected data through a scoping review of the capacity building of district health managers in sub-Saharan Africa (30), a review of documents related to the PHA reform in the DRC, and in-depth interviews with stakeholders of the PHA reform (Fig. 1).…”
Section: Data Collectionmentioning
confidence: 99%
“…We included all primary studies reporting leadership or management capacity building of district health managers in sub-Saharan Africa, written in English or French, and (d) published between 1st January 1987 and 13 October 2022. Further details on the scoping review can be found elsewhere (30).…”
Section: Scoping Reviewmentioning
confidence: 99%